Implementing a clinical-educator curriculum to enrich internal medicine residents’ teaching capacity - Yacob Habboush; Alexis Stoner; Claribel Torres; Sary Beidas (BMC Medical Education, 2019)
Abstract Introduction Physicians-in-training (residents) are typically the primary educators for medical students during clinical clerkships. However, residents are not formally trained to teach or to assess their teaching. The aim of this study was to assess the implementation of a clinical educator rotation aimed at developing residents’ competencies related to clinical teaching. Methods A mixed-methods approach was used to develop and assess the clinical educator rotation at a teaching community hospital. Internal medicine residents who participated in the rotation and consented to the research were assigned to the clinical educator trainee (CET) group, the remaining residents were assigned to the control group. Osteopathic medical students rotating in the medicine service line were invited to participate. The study used descriptive and qualitative analyses to measure primary and secondary outcomes. Results The primary outcome measure showed a positive change in resident knowledge, skills and behaviors in communication, reflection, feedback, precepting, and facilitation. Medical student perceptions of resident teaching skills confirmed the observed changes in CETs. Some CETs continued to practice and build their capacity for teaching after completing the rotation. Qualitatively, we derived four common themes among the data; communication, professional engagement, practice-based learning, and systems-based learning. Conclusion Resident teaching capacity was enriched after completing the clinical educator rotation. Other benefits included: enhanced patient communication and education, increased resident confidence, personal satisfaction with training, work life-balance and enhanced career satisfaction. Future research should focus on curricular content, faculty development, and delivery assessment. In addition, research efforts should identify appropriate emerging technologies to include in the curriculum for enhancing teaching capacity.